Suppression of circulating IgD+CD27+ memory B cells in infants living in a malaria-endemic region of Kenya - Asito Amolo S; Piriou Erwan; Jura Walter GZO; Ouma Collins; Odada Peter S; Ogola Sidney; Fiore Nancy; Rochford Rosemary (Malaria Journal, 2011)
Abstract Background Plasmodium falciparum infection leads to alterations in B cell subset distribution. During infancy, development of peripheral B cell subsets is also occurring. However, it is unknown if infants living a malaria endemic region have alterations in B cell subsets that is independent of an age effect. Methods To evaluate the impact of exposure to P. falciparum on B cell development in infants, flow cytometry was used to analyse the distribution and phenotypic characteristic of B cell subsets in infant cohorts prospectively followed at 12, 18 and 24 months from two geographically proximate regions in western Kenya with divergent malaria exposure i.e. Kisumu (malaria-endemic, n = 24) and Nandi (unstable malaria transmission, n = 21). Results There was significantly higher frequency and absolute cell numbers of CD19+ B cells in Kisumu relative to Nandi at 12(p = 0.0440), 18(p = 0.0210) and 24 months (p = 0.0493). No differences were observed between the infants from the two sites in frequencies of naïve B cells (IgD+CD27-) or classical memory B cells (IgD-CD27+). However, immature transitional B cells (CD19+CD10+CD34-) were higher in Kisumu relative to Nandi at all three ages. In contrast, the levels of non-class switched memory B cells (CD19+IgD+CD27+) were significantly lower overall in Kisumu relative to Nandi at significantly at 12 (p = 0.0144), 18 (p = 0.0013) and 24 months (p = 0.0129). Conclusions These data suggest that infants living in malaria endemic regions have altered B cell subset distribution. Further studies are needed to understand the functional significance of these changes and long-term impact on ability of these infants to develop antibody responses to P. falciparum and heterologous infections.